2014
DOI: 10.1111/tpj.12535
|View full text |Cite
|
Sign up to set email alerts
|

Selective regulation of the chitin‐induced defense response by the Arabidopsis receptor‐like cytoplasmic kinase PBL27

Abstract: These authors contributed equally to this work. SUMMARYRecognition of microbe-associated molecular patterns (MAMPs) initiates pattern-triggered immunity in host plants. Pattern recognition receptors (PRRs) and receptor-like cytoplasmic kinases (RLCKs) are the major components required for sensing and transduction of these molecular patterns. However, the regulation of RLCKs by PRRs and their specificity remain obscure. In this study we show that PBL27, an Arabidopsis ortholog of OsRLCK185, is an immediate down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
150
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(159 citation statements)
references
References 43 publications
(86 reference statements)
9
150
0
Order By: Relevance
“…Several members in subfamily VII including BIK1, PBL1, and PBL27 have been shown to function as important signaling components in plant immunity (Lu et al, 2010;Kadota et al, 2014;Li et al, 2014;Ranf et al, 2014;Shinya et al, 2014). In this study, we found two additional members in this subfamily, PCRK1 and PCRK2, which are also required for plant defense Figure 6.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Several members in subfamily VII including BIK1, PBL1, and PBL27 have been shown to function as important signaling components in plant immunity (Lu et al, 2010;Kadota et al, 2014;Li et al, 2014;Ranf et al, 2014;Shinya et al, 2014). In this study, we found two additional members in this subfamily, PCRK1 and PCRK2, which are also required for plant defense Figure 6.…”
Section: Discussionmentioning
confidence: 64%
“…It is phosphorylated by OsCERK1 after chitin treatment and is required for chitin-induced immune responses. A recent study showed that PBL27, an Arabidopsis ortholog of OsRLCK185, regulates chitin-induced defense responses in Arabidopsis (Shinya et al, 2014).…”
mentioning
confidence: 99%
“…Kinase-mediated immune regulation ranges from initial perception of MAMPs by transmembrane PRRs to mediating downstream immune signaling by RLCKs, calcium-dependent protein kinases, and MAPKs (Tena et al, 2011). The majority of characterized RLCK VII members function as positive regulators of MTI (Lu et al, 2010;Zhang et al, 2010;Yamaguchi et al, 2013;Ao et al, 2014;Shinya et al, 2014). In this study, we focused on the genetic and biochemical characterization of PBL13, an RLCK from subfamily VII possessing a unique C-terminal repeat motif.…”
Section: Discussionmentioning
confidence: 99%
“…RLCKs regulating MTI have been found to associate with PRR complexes and positively regulate immune responses in Arabidopsis and rice (Yamaguchi et al, 2013;Ao et al, 2014;Kadota et al, 2014;Li et al, 2014;Shinya et al, 2014). In light of the enhanced early MTI responses observed in the pbl13-2 KO, we reasoned that PBL13 may associate with PRR complexes to negatively regulate immune responses.…”
Section: Pbl13 Associates With Rbohd In Nicotiana Benthamianamentioning
confidence: 99%
See 1 more Smart Citation